A Evolução do fator de potência em residências e suas implicações para o setor elétrico - Neiva Pinheiro, Vinícius de Carvalho; Francato, Alberto Luiz (Latin American Journal of Energy Research, 2023)
In recent decades, electricity consumption patterns in residential buildings in Brazil have been going through changes, such as substitution of incandescent light bulbs to fluorescent or LED lamps, popularization of electronics and, to a certain extent, popularization of air conditioners. Devices that are not purely resistive consume, besides active energy, reactive power and, therefore, these changes in typical residential electric devices made reactive power consumption increase significantly more than active power consumption, demanding more reactive power provision from the grid. In this work, estimates of these changes in reactive power consumption in residences were made to evaluate their impacts to the Brazilian electricity sector. Results show that more detailed energy metering and billing systems for residential consumers may not only be fairer, but also encourage consume habits that alleviate reactive provision from the grid.